Composite rope knot temporary plugging agent for fracturing as well as preparation method and application of composite rope knot temporary plugging agent
By using composite fiber rope and hydrophobic coating design in the knot temporary plugging agent, combined with the use of blended fibers and functional polymers, the shortcomings of the existing knot temporary plugging agent in temperature, salt and pressure resistance are solved, and higher adaptability and construction performance are achieved.
Patent Information
- Application Number
- CN202311303828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-09
- Publication Date
- 2025-04-11
AI Technical Summary
The existing knot temporary plugging agents still cannot meet the needs in terms of temperature resistance, salt resistance, pressure resistance and active adaptability to perforation, especially in the fracturing process of low permeability tight oil and gas reservoirs.
The design of composite fiber rope combined with hydrophobic coating is adopted, and functional polymers are introduced to improve temperature and salt resistance, and the mechanical properties of the knot are enhanced by melt spinning and coating modification techniques.
It significantly improves the temperature, salt and pressure resistance of the knot temporary plugging agent, and can degrade completely, adapt to perforation of different sizes, and maintains a long degradation time in a high-temperature and high-salt environment to meet construction requirements.
Smart Images

Figure CN119799307A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tertiary oil recovery, and particularly relates to a composite knot temporary plugging agent for fracturing, a preparation method and application thereof. Background Art
[0002] my country's low-permeability oil reservoirs have a large amount of reserves that are difficult to mobilize and are difficult to develop. In addition, the low-permeability tight oil and gas reservoirs have a large regional span, diverse and complex geological structures, and some reservoirs are highly heterogeneous, with large differences in formation opening pressures. Fracturing and acidizing technology are the main means of developing such unconventional oil and gas reservoirs. Mechanical or chemical methods are usually required to transform the reservoir during fracturing or acidizing. These methods all have certain application limitations. For example, the use of bridge plugs and packers to temporarily plug perforations increases the cost of use, and is not applicable to situations where bridge plugs cannot be lowered and fracturing is difficult due to casing damage, necking, and casing leakage. The temporary plugging agents used in chemical methods are mostly granular, fiber, and gel-type temporary plugging agents. Granular temporary plugging agents have high plugging strength and a wide range of applicable temperatures, but they need to match the reservoir pores and throats, which increases the difficulty of construction; fiber temporary plugging agents have a wide range of applicable temperatures and mineralization, but the filter cake formed by the fibers has a certain porosity, low plugging strength, and is easily affected by the formation environment and incompletely degraded; gel temporary plugging agents are easy to inject, but are greatly affected by the formation environment, need to be broken after gelling, and are easy to pollute the formation. Knot-type temporary plugging agents are "hard and soft" temporary plugging agents, which are new temporary plugging agent products that have emerged in recent years. They have a wide range of applications and can form a good temporary plugging effect on perforations with irregular shapes and sizes.
[0003] The existing temporary plugging agent knot temporary plugging agent has a unique structure of a middle ball and two tail wings on both sides. It has a strong plugging effect and can be applied to the following scenarios: (1) Repeated fracturing of low-permeability new wells: New oil wells with low or ultra-low permeability often cannot meet the fracturing requirements after one fracturing. At this time, the use of traditional bridge plug transformation technology not only increases production costs, but is also not suitable for the transformation of ultra-long well sections. The use of knot temporary plugging agents can merge multiple perforation sections into one section for temporary plugging and repeated fracturing, thereby achieving the purpose of repeated fracturing transformation. (2) Repeated fracturing of old wells with reduced permeability: Due to long-term exploitation, the cracks in old wells gradually close under the action of formation pressure, resulting in a decrease in permeability. The knot temporary plugging agent can be used to temporarily plug some perforations, and fracturing can be performed on the unplugged perforations to achieve the purpose of transforming the formation. (3) Transformation of perforation clusters in oil and gas wells: During the oil and gas development process, 1 / 3 to 1 / 2 of the perforation clusters in the entire well section of some oil and gas wells are not effectively opened, which greatly affects the production. The knot temporary plugging agent can first plug the intact perforations, increase the pressure in the well, flush the unopened perforations, and effectively open the perforation clusters to increase production. (4) General fracturing of special well sections: In some cases where the bridge plug cannot be lowered due to casing damage, necking, and casing leakage, and fracturing is difficult, the knot temporary plugging agent is used to replace the traditional lowered bridge plug or soluble bridge plug to temporarily plug the perforation clusters. General fracturing operations can be performed on the perforation clusters that cannot be reached to improve production efficiency.
[0004] However, the existing knot temporary plugging agents of this type still cannot meet the requirements in terms of temperature resistance, salt resistance, pressure resistance and active adaptability to perforation and are in urgent need of improvement. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a composite knot temporary plugging agent for fracturing that is resistant to temperature and salt, has high pressure bearing capacity, strong adaptability and is fully degradable, as well as a preparation method and application thereof.
[0006] In a first aspect of the present invention, a composite knot temporary plugging agent for fracturing is provided, which comprises a composite fiber rope and a hydrophobic coating attached to the surface of the composite fiber rope; the composite fiber rope is formed by mixing and weaving a blended fiber and a degradable fiber; the blended fiber is formed by melt spinning a functional polymer and polylactic acid, and the functional polymer has a structure as shown in formula (1):
[0007]
[0008] As a specific embodiment of the present invention, the method for preparing the functional polymer comprises: mixing a polymerization monomer, water, an initiator, EDTA and a urea solution to react under an inert atmosphere;
[0009] Preferably, the polymerizable monomers include the following components in parts by weight: 0.05-0.2 parts of dimethylaminoethyl methacrylate-dodecyl bromide, 0.1-0.3 parts of methacryloxypropyltrimethoxysilane, 5-8 parts of 1-vinyl-2-pyrrolidone, and 12-14 parts of 2-acrylamide-2-methylpropanesulfonic acid;
[0010] Preferably, the initiator is an azo initiator, preferably any one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, and azobisisobutylimidazoline hydrochloride;
[0011] Preferably, the reaction temperature is 40-60°C and the reaction time is 5-10h;
[0012] Preferably, in the reaction solution, the concentration of the polymerizable monomer is 20 to 30% wt;
[0013] Preferably, the amount of the initiator used is 0.1-2.0% based on the total weight of the polymerizable monomers.
[0014] As a specific embodiment of the present invention, the preparation method of the blended fiber includes: blending the functional polymer with polylactic acid particles, and then performing melt spinning;
[0015] Preferably, the mass ratio of the functional polymer to the polylactic acid particles is 1:19-99, preferably 1:19;
[0016] Preferably, in the melt spinning, the melt spinning temperature is 180-250° C., the drawing multiple is 3-5 times, the drawing temperature is 70-110° C., and the winding speed is 400-1000 m / min.
[0017] As a specific embodiment of the present invention, the degradable fiber is chitosan fiber, which has good rigidity.
[0018] As a specific embodiment of the present invention, the mass ratio of the blended fiber to the chitosan fiber is 1:9-99, preferably 1:9-19.
[0019] As a specific embodiment of the present invention, the material of the hydrophobic coating is selected from any one or more of modified silicone oil and liquid paraffin.
[0020] The second aspect of the present invention provides a method for preparing the composite knot temporary plugging agent for fracturing, comprising:
[0021] S1. Twisting the blended fiber and the degradable fiber, and then weaving them into a rope, tying the rope into a knot in the middle, with a section of loose rope ends left at each end, to obtain a composite fiber rope;
[0022] S2. Soak the composite fiber rope in a hydrophobic solution and then dry it to obtain a composite rope knot temporary plugging agent for fracturing.
[0023] As a specific embodiment of the present invention, the hydrophobic solution is selected from any one or more of modified silicone oil and liquid paraffin.
[0024] As a specific embodiment of the present invention, the soaking time is more than 24 hours.
[0025] The third aspect of the present invention provides the use of the aforementioned composite knot temporary plugging agent for fracturing in the fracturing of low-permeability tight oil and gas reservoirs.
[0026] The beneficial effects of the present invention are:
[0027] 1) The knot temporary plugging agent provided by the present invention particularly introduces a functional polymer of the structure shown in formula (1), which is a tetrapolymer of 1-vinyl-2-pyrrolidone (NVP), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), dimethylaminoethyl methacrylate-dodecyl bromide (DMDB) and methacryloxypropyltrimethoxysilane (KH570). NVP and AMPS are introduced to improve the temperature and salt resistance of the composite knot temporary plugging agent, DMDB is introduced to give the polymer hydrophobic association and emulsification capabilities, making it more compatible with subsequent oily coatings, and KH570 is introduced to obtain a micro-crosslinked structure to improve the mechanical properties of the knot. The present invention significantly improves the heat resistance, salt resistance and pressure bearing performance and can be fully degraded by blending the functional polymer and polylactic acid for melt spinning, and then mixing with degradable fibers for weaving, cutting and coating modification. The test confirms that the rope knot temporary plugging agent of the present invention has a long degradation time in environmental saline (NaCl 5000mg / L) at a temperature of 60 to 150°C, and its heat resistance, salt resistance and degradation performance can better meet the construction requirements. Compared with the existing temporary plugging balls, the rope knot temporary plugging agent of the present invention has a unique appearance structure, more thorough degradation, no damage to the reservoir, stronger adaptability to irregular perforations, and better sealing performance.
[0028] 2) The preparation method of the knot temporary plugging agent provided by the present invention is simple and easy to operate, and the production parameters can be quickly adjusted according to the actual situation on site, which is convenient for the improved production of subsequent products. By adjusting the size of the middle knot and the thickness and length of the rope ends at both ends, perforations of different sizes can be temporarily plugged. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the infrared spectrum of the functional polymer of the present invention;
[0030] Figure 2 This is a real picture of the composite knot temporary plugging agent for fracturing of the present invention. DETAILED DESCRIPTION
[0031] The content of the present invention is described in detail below with reference to specific drawings and embodiments. The examples described below are only preferred embodiments of the present invention. It should be noted that the following description is only for the purpose of explaining the present invention, and does not impose any form of limitation on the present invention. Any simple modification, equivalent changes and modifications made to the implementation methods based on the technical essence of the present invention are within the scope of the technical solution of the present invention. In the following embodiments, AMPS: 2-acrylamide-2-methylpropanesulfonic acid; DMDB: dimethylaminoethyl methacrylate-dodecyl bromide; NVP: 1-vinyl-2-pyrrolidone; KH570: methacryloxypropyltrimethoxysilane; the materials, reagents, etc. used, unless otherwise specified, are obtained from commercial sources.
[0032] Example 1
[0033] S101, Synthesis of functional polymers: Add a certain amount of deionized water to a three-necked flask, and accurately weigh 14g of AMPS, 0.1g of DMDB, and 5.7g of NVP in turn and place them in the reaction flask to quickly dissolve the above monomers; use a stirrer to fully stir the monomers in the beaker, and drop 0.2g of KH570 monomer; after the dropwise addition is completed, maintain at 50°C, and use a pipette to accurately transfer a certain amount of diisobutylamidine hydrochloride, EDTA and urea solution; use 2mol / L NaOH or HCl solution to adjust the pH value to 7-8; transfer the above monomer solution into a polymerization bottle, pass nitrogen for 30 minutes to drive out oxygen, and react for 5 hours. After the reaction is completed, take out the gel-like polymerization product, cut it into small pieces with scissors, and rinse it with ethanol several times; dry it in a blast drying oven at 60°C for 24 hours, then crush the product to obtain a powdery white solid, which is the functional polymer;
[0034] S102, melt composite spinning and weaving: melt-blending and spinning the functional polymer and polylactic acid particles obtained in step S101 at a mass ratio of 5:95 using a melt spinning machine, the melt spinning temperature is 200°C, the drafting multiple is 3 times, the drafting temperature is 70°C, and the winding speed is 500m / min to obtain a blended fiber; the blended fiber and chitosan fiber are twisted together at a mass ratio of 1:9 to prepare a composite wire, and a temporary plugging agent thread end with uniform thickness is prepared; then the temporary plugging agent thread end is woven into a temporary plugging agent rope; then the temporary plugging agent rope is knotted and the rope ends at both ends of the knot are loosened, the knot diameter and the tassel length are adjusted, and the composite fiber rope is cut;
[0035] S103, coating modification and drying: the composite fiber rope obtained in step S102 is immersed in liquid paraffin for 24 hours, and dried at 50° C. to obtain a composite rope knot temporary plugging agent for fracturing.
[0036] Example 2
[0037] S201, Synthesis of functional polymers: Add a certain amount of deionized water to a three-necked flask, and accurately weigh 12g of AMPS, 0.1g of DMDB, and 7.7g of NVP in turn and place them in the reaction flask to quickly dissolve the above monomers; use a stirrer to fully stir the monomers in the beaker, and drop 0.2g of KH570 monomer; after the dropwise addition is completed, maintain at 50°C, and use a pipette to accurately transfer a certain amount of diisobutylamidine hydrochloride, EDTA, and urea solution; use 2mol / L NaOH or HCl solution to adjust the pH value to 7-8; transfer the above monomer solution into a polymerization bottle, pass nitrogen for 30 minutes to drive out oxygen, and react for 5 hours. After the reaction is completed, take out the gel-like polymerization product, cut it into small pieces with scissors, and rinse it with ethanol several times; dry it in a blast drying oven at 60°C for 24 hours, then crush the product to obtain a powdery white solid, which is the functional polymer;
[0038] S202, melt composite spinning and weaving: melt-blending and spinning the functional polymer and polylactic acid particles obtained in step S201 at a mass ratio of 5:95 using a melt spinning machine, the melt spinning temperature is 200°C, the drafting multiple is 3 times, the drafting temperature is 70°C, and the winding speed is 500m / min to obtain a blended fiber; the blended fiber and chitosan fiber are twisted at a mass ratio of 1:9 to prepare a composite wire, and a temporary plugging agent thread end with uniform thickness is prepared; then the temporary plugging agent thread end is woven into a temporary plugging agent rope; then the temporary plugging agent rope is knotted and the rope ends at both ends of the knot are loosened, the knot diameter and the tassel length are adjusted, and the composite fiber rope is cut;
[0039] S203, coating modification and drying: the composite fiber rope obtained in step 202 is immersed in liquid paraffin for 24 hours, and dried at 50° C. to obtain a composite rope knot temporary plugging agent for fracturing.
[0040] Example 3
[0041] S301, Synthesis of functional polymers: Add a certain amount of deionized water to a three-necked flask, and accurately weigh 14g of AMPS, 0.1g of DMDB, and 5.7g of NVP in turn and place them in the reaction flask to quickly dissolve the above monomers; use a stirrer to fully stir the monomers in the beaker, and drop 0.2g of KH570 monomer; after the dropwise addition is completed, maintain at 50°C, and use a pipette to accurately transfer a certain amount of diisobutylamidine hydrochloride, EDTA, and urea solution; use 2mol / L NaOH or HCl solution to adjust the pH value to 7-8; transfer the above monomer solution into a polymerization bottle, pass nitrogen for 30 minutes to drive off oxygen, and react for 5 hours. After the reaction is completed, take out the gel-like polymerization product, cut it into small pieces with scissors, and rinse it with ethanol several times; dry it in a blast drying oven at 60°C for 24 hours, then crush the product to obtain a powdery white solid;
[0042] S302, melt composite spinning and weaving: melt-blending and spinning the functional polymer and polylactic acid particles obtained in step 301 at a mass ratio of 5:95 using a melt spinning machine, the melt spinning temperature is 200°C, the drafting multiple is 3 times, the drafting temperature is 70°C, and the winding speed is 500m / min to obtain a blended fiber; the blended fiber and chitosan fiber are twisted at a mass ratio of 5:95 to prepare a composite wire, and a temporary plugging agent thread end with uniform thickness is prepared; then the temporary plugging agent thread end is woven into a temporary plugging agent rope; then the temporary plugging agent rope is knotted and the rope ends at both ends of the knot are loosened, the knot diameter and the tassel length are adjusted, and the composite fiber rope is cut;
[0043] S303, coating modification and drying: the composite fiber rope obtained in step 302 is immersed in liquid paraffin for 24 hours, and dried at 50° C. to obtain a composite rope knot temporary plugging agent for fracturing.
[0044] Example 4
[0045] S401, Synthesis of functional polymers: Add a certain amount of deionized water to a three-necked flask, and accurately weigh 14g of AMPS, 0.1g of DMDB, and 5.7g of NVP in turn and place them in the reaction flask to quickly dissolve the above monomers; use a stirrer to fully stir the monomers in the beaker, and drop 0.2g of KH570 monomer; after the dropwise addition is completed, maintain at 50°C, and use a pipette to accurately transfer a certain amount of diisobutylamidine hydrochloride, EDTA, and urea solution; use 2mol / L NaOH or HCl solution to adjust the pH value to 7-8; transfer the above monomer solution into a polymerization bottle, pass nitrogen for 30 minutes to drive off oxygen, and react for 5 hours. After the reaction is completed, take out the gel-like polymerization product, cut it into small pieces with scissors, and rinse it with ethanol several times; dry it in a blast drying oven at 60°C for 24 hours, then crush the product to obtain a powdery white solid, which is the functional polymer;
[0046] S402, melt composite spinning and weaving: melt-blending and spinning the functional polymer and polylactic acid particles obtained in step 401 according to a mass ratio of 5:95 using a melt spinning machine, the melt spinning temperature is 210°C, the drafting multiple is 5 times, the drafting temperature is 70°C, and the winding speed is 1000m / min to obtain a blended fiber; the blended fiber and chitosan fiber are twisted together at a mass ratio of 1:9 to prepare a composite wire, and a temporary plugging agent thread end with uniform thickness is prepared; then the temporary plugging agent thread end is woven into a temporary plugging agent rope; then the temporary plugging agent rope is knotted and the rope ends at both ends of the knot are loosened, the knot diameter and the tassel length are adjusted, and the composite fiber rope is cut;
[0047] S403, coating modification and drying: the composite temporary plugging agent obtained in step 402 is immersed in liquid paraffin for 24 hours to obtain a composite temporary plugging agent product, and then dried at 50° C. to obtain a final temporary plugging agent product.
[0048] Example 5
[0049] S501, Synthesis of functional polymers: Add a certain amount of deionized water to a three-necked flask, and accurately weigh 14g of AMPS, 0.1g of DMDB, and 5.7g of NVP in turn and place them in the reaction flask to quickly dissolve the above monomers; use a stirrer to fully stir the monomers in the beaker, and drop 0.2g of KH570 monomer; after the dropwise addition is completed, maintain at 50°C, and use a pipette to accurately transfer a certain amount of diisobutylamidine hydrochloride, EDTA and urea solution; use 2mol / L NaOH or HCl solution to adjust the pH value to 7-8; transfer the above monomer solution into a polymerization bottle, pass nitrogen for 30 minutes to drive off oxygen, and react for 5 hours. After the reaction is completed, take out the gel-like polymerization product, cut it into small pieces with scissors, and rinse it with ethanol several times; dry it in a blast drying oven at 60°C for 24 hours, then crush the product to obtain a powdery white solid, which is the functional polymer;
[0050] S502, melt composite spinning and weaving: melt-blending and spinning the functional polymer and polylactic acid particles obtained in step 501 at a mass ratio of 5:95 using a melt spinning machine, the melt spinning temperature is 200°C, the drafting multiple is 3 times, the drafting temperature is 70°C, and the winding speed is 500m / min to obtain a blended fiber; the blended fiber and chitosan fiber are twisted at a mass ratio of 1:9 to prepare a composite wire, and a temporary plugging agent thread end with uniform thickness is prepared; then the temporary plugging agent thread end is woven into a temporary plugging agent rope; then the temporary plugging agent rope is knotted and the rope ends at both ends of the knot are loosened, the knot diameter and the tassel length are adjusted, and the composite fiber rope is cut;
[0051] S503, coating modification and drying: the composite fiber rope obtained in step 502 is immersed in liquid paraffin for 24 hours, and dried at 50° C. to obtain a composite rope knot temporary plugging agent for fracturing.
[0052] The infrared spectrum of the functional polymer prepared in Example 1 of the present invention is as follows: Figure 1 As shown, 3417cm -1 It is the characteristic absorption peak of NH, 2921cm -1 and 2844cm -1 The characteristic absorption peaks of methyl and methylene in the polymer main chain and surfactant monomers are 1720 cm -1 The carbonyl characteristic absorption peak is 1465 cm -1 and 1373cm -1 -CH2- and -CH3 bending vibration peaks, 1299 cm -1 It is the characteristic absorption peak of CN, 1168cm -1 The characteristic absorption peak of CO in the ester group is 1027 cm -1 It is the characteristic absorption peak of S=O, 719cm-1 It is the bending vibration peak of (CH2)n with more than four carbon numbers, 651cm -1 It is the characteristic absorption peak of sulfonic acid group, 576cm -1 , no obvious C=C characteristic absorption peak appeared in the sample, indicating that copolymerization occurred in the sample.
[0053] The composite knot temporary plugging agent for fracturing prepared in the above Examples 1 to 5 was used as a test sample, and the complete degradation time was tested in environmental brine (NaCl 5000 mg / L) at temperatures of 60 to 100° C. and 100 to 150° C. The specific results are shown in Table 1 below:
[0054] Table 1 Performance test results
[0055]
[0056] It can be seen from Table 1 that the knot temporary plugging agent of the present invention has a long degradation time in environmental saline (NaCl 5000 mg / L) at 60-150°C, which shows that its temperature and salt resistance and degradation performance can better meet the construction requirements.
[0057] The composite knot temporary plugging agent for fracturing prepared in the above Examples 1 to 5 was used as the test sample. The knot temporary plugging agents were placed on the pressure plate one by one, and then the pressure was applied when the pressure plate and the ball were in contact. The pressure value at the moment the ball was broken was recorded, and the steps were repeated to read the pressure value at the moment of breaking. For some knot temporary plugging agents that became flat after being damp or broke at the beginning of pressure application, the experimental results were considered invalid. The specific results are shown in Table 2:
[0058] Table 2 Pressure bearing performance test results
[0059] pressure Example 1 Example 2 Example 3 Example 4 Example 5 50MPa intact intact intact intact intact 60MPa intact intact intact intact intact 70MPa broken intact broken broken intact
[0060] It can be seen from Table 2 that the knot temporary plugging agents of various embodiments of the present invention remain intact within the pressure range of 50-60 MPa and have good pressure-bearing capacity, and the knot temporary plugging agents of Embodiments 2 and 5 have the best pressure-bearing capacity and can still remain intact under a pressure of 70 MPa.
[0061] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations, improvements, deductions, and substitutions can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.
Claims
1. A composite knot temporary plugging agent for fracturing, characterized in that: It includes a composite fiber rope and a hydrophobic coating attached to the surface of the composite fiber rope; The composite fiber rope is formed by mixing and weaving a blended fiber and a degradable fiber; the blended fiber is formed by melt-spinning a functional polymer and polylactic acid, and the functional polymer has a structure as shown in formula (1):
2. The composite knot temporary plugging agent for fracturing according to claim 1, characterized in that: The method for preparing the functional polymer comprises: mixing a polymerization monomer, water, an initiator, EDTA and a urea solution to react under an inert atmosphere; Preferably, the polymerizable monomer comprises the following components in parts by weight: 0.05-0.2 parts of dimethylaminoethyl methacrylate-dodecyl bromide, 0.1-0.3 parts of methacryloxypropyltrimethoxysilane, 5-8 parts of 1-vinyl-2-pyrrolidone, and 12-14 parts of 2-acrylamide-2-methylpropanesulfonic acid; Preferably, the initiator is an azo initiator, preferably any one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, and azobisisobutylimidazoline hydrochloride; Preferably, the reaction temperature is 40-60°C and the reaction time is 5-10h; Preferably, in the reaction solution, the concentration of the polymerizable monomer is 20 to 30% wt; Preferably, the amount of the initiator used is 0.1-2.0% based on the total weight of the polymerizable monomers.
3. The composite knot temporary plugging agent for fracturing according to claim 1, characterized in that: The preparation method of the blended fiber comprises: blending a functional polymer with polylactic acid particles, and then performing melt spinning; Preferably, the mass ratio of the functional polymer to the polylactic acid particles is 1:19-99, preferably 1:19; Preferably, in the melt spinning, the melt spinning temperature is 180-250° C., the drafting multiple is 3-5 times, the drafting temperature is 70-110° C., and the winding speed is 400-1000 m / min.
4. The composite knot temporary plugging agent for fracturing according to claim 1, characterized in that: The degradable fiber is chitosan fiber.
5. The composite knot temporary plugging agent for fracturing according to claim 4, characterized in that: The mass ratio of the blended fiber to the chitosan fiber is 1:9-99, preferably 1:9-19.
6. The composite knot temporary plugging agent for fracturing according to claim 1, characterized in that: The material of the hydrophobic coating is selected from any one or more of modified silicone oil and liquid paraffin.
7. A method for preparing the composite knot temporary plugging agent for fracturing according to any one of claims 1 to 6, characterized in that: The preparation method comprises: S1. Twisting the blended fiber and the degradable fiber, and then weaving them into a rope, tying the rope into a knot in the middle, with a section of loose rope ends left at each end, to obtain a composite fiber rope; S2. Soaking the composite fiber rope in a hydrophobic solution and then drying it to obtain the composite rope knot temporary plugging agent for fracturing.
8. The preparation method according to claim 7, characterized in that: The hydrophobic solution is selected from any one or more of modified silicone oil and liquid paraffin.
9. The preparation method according to claim 7, characterized in that: The soaking time is more than 24 hours.
10. Use of the composite knot temporary plugging agent for fracturing according to any one of claims 1 to 6 in fracturing of low-permeability tight oil and gas reservoirs.